2023
DOI: 10.2144/fsoa-2023-0042
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Lockdown

Hafez Al-Momani,
Dua'a Al Balawi,
Muna Almasri
et al.

Abstract: Aim: This study examines the changes in gastroesophageal reflux disease (GERD) symptom frequency among patients with GERD throughout the COVID-19 pandemic. Methods: A structured questionnaire was distributed among 198 GERD patients. The questionnaire consisted of a demographic characteristic assessment, the GerdQ questionnaire, and a reflux symptom index (RSI) questionnaire. Result & conclusion: A statistically significant increase in GerdQ score was identified among participants during the COVID-19 pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…For example, stress and emotional states can affect gastrointestinal function leading to gastrointestinal disease [7]. Previous studies have shown that the factors associated with the incidence of GERD in resident doctors during the COVID-19 pandemic are the burden factors of education, diet, and psychosocial economy [21]. This study assessed the typical symptoms (heartburn and regurgitation) and atypical symptoms (nausea, sleep disturbances at night, abdominal pain, and consumption of additional drugs) to determine the possibility of GERD.…”
Section: Resultsmentioning
confidence: 99%
“…For example, stress and emotional states can affect gastrointestinal function leading to gastrointestinal disease [7]. Previous studies have shown that the factors associated with the incidence of GERD in resident doctors during the COVID-19 pandemic are the burden factors of education, diet, and psychosocial economy [21]. This study assessed the typical symptoms (heartburn and regurgitation) and atypical symptoms (nausea, sleep disturbances at night, abdominal pain, and consumption of additional drugs) to determine the possibility of GERD.…”
Section: Resultsmentioning
confidence: 99%
“…In an Indonesian survey comprising 9,800 patients, it was found that there was an increased rate of GERD during the pandemic compared to the prepandemic period (67.9% vs. 61.8%, respectively, p<0.001) [12]. Other investigators attribute the worsening GERD symptoms to the restrictive lockdown measures during the pandemic [13]. New-onset GERD symptoms post-COVID-19 infection may last over a year and may persist for the long term [14].…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 , 35 ] However, Only 1 study has examined the changes in GERD synonyms during the COVID-19 epidemic and lockdown. [ 36 ]…”
Section: Gerd and Covid-19 Lockdown Measuresmentioning
confidence: 99%
“…This research [ 36 ] involved 210 people with preexisting GERD diagnoses and the findings highlighted a statistically significant increase in the frequency of GERD symptoms during the pandemic. Most participants in Al-Momani, Balawi, Almasri, AlGhawrie, Ibrahim, Adli, Balawi and Haj Mahmoud [ 36 ] study reported an increased frequency of heartburn and regurgitation during the pandemic, along with increased difficulties falling asleep and increased medicine need for their symptoms.…”
Section: Gerd and Covid-19 Lockdown Measuresmentioning
confidence: 99%
See 1 more Smart Citation